Respuesta :
Answer:
- 15
Step-by-step explanation:
Given f(x) divided by (x + h) then the remainder is the value of f(- h)
Here
f(x) = 3x³ - 5x² - 47x + k ← k is the constant term , then
f(- 3) = 3(- 3)³ - 5(- 3)² - 47(- 3) + k = 0 , that is
3(- 27) - 5(9) + 141 + k = 0
- 81 - 45 + 141 + k = 0
15 + k = 0 ( subtract 15 from both sides )
k = - 15
Answer: The missing value is -15 (negative 15)
Step-by-step explanation: Well start off with long division and see how far you get before you run into the constant term you're looking for. The answer entirely is 3x^2 -14x -5 when solved and ensuring there is no remainder that follows after